Age sensitive associations of adolescent substance use with amygdalar, ventral striatum, and frontal volumes in young adulthood. (1st May 2018) - Windle, Michael; Gray, Joshua C.; Lei, Karlo Mankit; Barton, Allen W.; Brody, Gene; Beach, Steven R.H.; Galván, Adrianna; MacKillop, James; Clark, Uraina S.; Sweet, Lawrence H.
Highlights: MRI brain volumes were assessed among young adult African Americans. Early adolescent substance use was associated with smaller amygdalar volume. Middle adolescent substance use was associated with smaller pars opercularis volume. Findings support age sensitive periods of brain development for substance use. Abstract: Introduction: This study evaluated an age sensitive model of substance use across adolescence to determine if substance use was associated with smaller volumes for an earlier developing brain region, the amygdala, a later developing region, the inferior frontal gyrus, and the ventral striatum. Method: Participants ( N  = 110) were African American young adults who were members of a longitudinal cohort across childhood and adolescence. Measures of substance use were collected across early (ages 12–15 yrs.), middle (ages 16–18 yrs.), and later (ages 19–21 yrs.) adolescence; then, at age 25, a representative subset of the sample completed magnetic resonance imaging (MRI) that assessed regional brain volumes. Results: Higher levels of substance use during early adolescence, but not middle or later adolescence, were significantly associated with smaller amygdalar volume in young adulthood. Higher levels of substance use during middle adolescence, but not early or later adolescence, were significantly associated with smaller pars opercularis volume. Substance use was not associated with the pars triangularis or ventral striatum. Conclusion: These findings support age sensitive associations between substance use and smaller gray matter volumes at age 25 and are consistent with literature supporting the differential nature of substance use and brain maturation across adolescence and into young adulthood.